Islamic Banks: Analysis of the Rules of Fiqh on the Fatwa of the National Sharia Board-Indonesian Ulama Council - Mahmud Yusuf; Hasanudin Hasanudin; Fathurrahman Azhari; Muhammad Rahmani Abduh; Sri Ana Farhanah (International Journal of Law, Environment, and Natural Resources, 2023)
Both directly and indirectly, Sharia banking regulations in Indonesia are heavily influenced by the Fatwa of the National Sharia Council-Indonesian Ulema Council. In its fatwas, the National Sharia Council-Indonesian Ulema Council cites many fiqh principles as one of its legal foundations which shows that fiqh rules occupy a crucial position in the fatwas issued by the National Sharia Council-Indonesian Ulema Council. But unfortunately, research and scientific studies related to fiqh principles are currently still relatively few and receive less attention from academics. Therefore, this study aims to find out how fiqh principles are used in the National Sharia Council-Indonesian Ulema Council fatwas related to sharia banking to fill the void in scientific studies and attract scientific interest in this field. This research is normative legal research/legal research. The data used in this study were obtained from the Sharia Banking Fatwa Association compiled by the National Sharia Council-Indonesian Ulema Council. The data is then analyzed using a qualitative content analysis technique, which analyzes the contents of various texts and then systematically transforms them into a very organized and concise main summary. The results of this study indicate that from 2000 to 2018, the National Sharia Council-Indonesian Ulema Council issued 90 fatwas related to Islamic banking. Of the 90 fatwas, 87 fatwas used fiqh principles as one of their legal foundations. Overall, the fiqh principles used in the National Sharia Council-Indonesian Ulema Council Fatwa regarding Islamic banking total 39 principles with a frequency of use of 266 times. Where the rule "Basically, all forms of muamalah may be carried out unless there is an argument that forbids it" is the rule most often used with a frequency of use of 85 times and Fatwa 118/DSN-MUI/II/2018 concerning Guidelines for Guaranteeing Deposits for Customers of Sharia Banks is a fatwa that the most use of fiqh rules is as many as 11 rules. Then, the generalization of the 39 fiqh principles used in the National Sharia Council-Indonesian Ulema Council Fatwa regarding sharia banking has at least produced several theories, namely the theory of origin law, the theory of maslahat, the customary theory, the Khilafah theory, the wasilah theory, the promise theory, the majority theory, and several another theory. In addition, the National Sharia Council-Indonesian Ulema Council fatwas related to sharia banking has also made a positive contribution to the development of sharia banking in Indonesia. Finally, for future researchers, we provide suggestions in the form of future research related to the principles of fiqh and the National Sharia Council-Indonesian Ulema Council Fatwa.